(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The influence of electromagnetic irradiation by extremely high frequencies 41.8 GHz and 51.8 GHz (EMI EHF) on chemiluminescence (H2O2–Cl) intensity, malondialdehyde (MDA) content and catalase activity in wheat shoots cells has been investigated. It has been shown that this irradiation impacts on lipids oxidation of cellular membranes of plant seedlings and leads to intensity increasing of freeradical processes, measured by CL. It has also been shown that at multiple irradiation of wheat seedlings the increasing of MDA rate is observed. At the same time EMI-induced oxidative stress was indicated by markedly change of catalase activity depending on EMI frequency used and exposure duration.